Postliberal theology and the church catholic : conversations with George Lindbeck, David Burrell, and Stanley Hauerwas - Wright, John W.; Lindbeck, George A.; Burrell, David B.; Hauerwas, Stanley, 1940- (Grand Rapids, Mich : Baker Academic, 2012)
How does postliberalism relate to Roman Catholic theology? More specifically, how reliant is postliberalism on what happened at Vatican II? This work examines the Roman Catholic roots of postliberal theology, centering on conversations with three of the most important North American theologians in the last half of the twentieth century.
Introduction: Back to the future -- The silent shifting of tectonic plates -- "I pray that they might be one as we are one" : an interview with George Lindbeck -- "In the beginning, God created the heavens and the earth" : an interview with David Burrell -- "Blessed be the peacemakers, for they shall see God" : an interview with Stanley Hauerwas -- Israel, judgment, and the future of the church catholic : a dialogue among friends -- Conclusion: The appeal of witnesses.
Includes bibliographical references and index.
Keywords: Burrell, David B. -- Interviews; Hauerwas, Stanley, -- 1940- -- Interviews; Postliberal theology; Church -- Unity; Theologians -- United States -- Interviews